Development of solid rocket propellant - Mohammad Norshim, Mohamed Hashim (2012)
This thesis presents a study on development of solid rocket propellant that was carried out at Universiti Malaysia Pahang. Rocket propellant has been identified as a component that played an important role in the development of rockets. The ejected material in rocket propulsion is due to material called propellant. Without propellant, a rocket cannot be launched. A solid rocket is a class of rocket in which the fuel, oxidizer and binder are mixed together and cast into a solid material. Objective of this thesis is to produce potassium nitrate sucrose based solid rocket propellant. Materials used to produce this propellant are potassium nitrate powder and sucrose powder. Potassium nitrate is an oxidizer in the propellant material and sucrose as a fuel in the propellant. This propellant is produce using the method of formation. This method was easy to operate and cost effective. Burning rate test was carried out at 1 atm and 7 atm pressure using a different oxidizer/fuel mass ratio. At 1 atm pressure, it was found that burning rate for the ratio of 65/35 was 2.184 mm/sec. At 7 atm, it was found that burning rate for the ratio 65/35 was 3.791 mm/sec. Propellant must be kept in a cool dry place like it in the refrigerator to prevent it become melt. From the result of this research, the burning rate test rig has been successfully designed, fabricated and tested. As a conclusion, oxidizer / fuel ratio and combustion pressure influence burning rate test.